A Tale of the Unexpected: The Ending of 2 Kings 3 Re-Examined - Gilmour, Rachelle (Australian biblical review, 2017)
This article proposes that the failure of Israel to gain victory over Moab at the ending of 2 Kings 3 is not a surprise in the narrative but the resolution of a structure of suspense. It is shown that there are two possible outcomes to the initiating event of Moab's rebellion--Israel's success or Israel's failure--and that the course of events plays upon the audience's expectations for which of these two outcomes will take place at the story's resolution. Two other "surprises" at the story's conclusion will also be re-examined: Elisha's apparently unfulfilled prophecy and the sudden appearance of "wrath," causing Israel to withdraw.